Redo surgery or carotid stenting for restenosis after carotid endarterectomy: results of two different treatment strategies - Attigah, Nicolas; Külkens, Sonja; Deyle, Claudia; Ringleb, Peter A.; Hartmann, Marius; Geisbüsch, Philipp; Böckler, Dittmar (Annals of vascular surgery, 2010)
Background - We evaluated retrospectively early and midterm results of conventional redo surgery and carotid stent-assisted angioplasty (CAS) in the treatment of carotis restenosis (CR) after carotid endarterectomy (CEA). - Methods - From January 1989 to April 2007, 79 consecutive patients (61 male, median age 65 years, range 51-82) were treated for CR. Seven patients were treated for bilateral CR, accounting for 86 reconstructions, 41 CEAs, and 45 CAS procedures. Fifty (58.1%) CRs were asymptomatic, and 36 (41.9%) CRs were symptomatic. Treatment for CR was recommended for any stenosis >70% based on duplex ultrasound imaging with a peak systolic flow of >200cm/sec. - Results - There was no difference in age in the two groups. The incidence of atherosclerotic risk factors and comorbidity was similar in the two groups. All patients received aspirin as basic medical treatment, and 53 patients (61.6%) were on statin therapy. The time period from primary CEA to reoperation or CAS was significantly shorter in the CAS group than in the CEA group (54.1 vs. 85.34 months, p=0.003). Correspondingly, the proportion of early CR was significantly higher in the CAS group as well (20 vs. 5, p=0.001). There was no perioperative mortality (30 days) in the two groups. In the CEA group, four neurological complications were seen versus one in the CAS group (p=0.13). Wound site and cardiac complication rates were significantly higher in the CEA group (p=0.029) with a median follow-up of 35 months (range 12-190). The overall actuarial survival after 60 months was 83% in the CEA group and 100% in the CAS group (p=0.87). Freedom from repeat intervention for re-recurrence was 89% in the CEA group and 95% in the CAS group (p=0.52). - Conclusion - CAS is feasible and safe in treating CR. Furthermore, midterm overall survival and need for treatment of re-recurrence is equal to CEA. However, reoperation is an established option and remains the treatment of choice when contraindications for CAS are evident.